U.V light effect on the mechanical behaviour of HDPE/Carbon black composites - Sahu, Alok K.; Sudhakar, Kumarasamy; Sarviya, Rishindra Mohan (Institute of Physics Publishing, 2020)
Energy is one of the most essential parts of our universe. Energy has come to be known as a 'strategic commodity' and any uncertainty about its supply can threaten the functioning of the entire economy. Sun is the plentiful source of energy freely & enormously available throughout the world. Solar energy is considered to be one of the more encouraging energy alternatives due to its ubiquity and sustainability. In solar energy floating solar power system is a revolutionary step as it can solve the perennial problem of land. In floating solar structure, floats made of HDPE material are used. The Ultra Violet (UV) rays present in the natural environment degrades HDPE materials. In the present study, the composite of HDPE material with concentration of 1%, 2% & 3% carbon black is used for making composites. The carbon black acts as UV stabilizer. The mechanical behaviour of the HDPE/Carbon black composite floats are analysed before and after U.V exposure. Properties like Tensile Strength, Breakpoint, Flexural Strength, Flexural Modulus, Impact Resistance, Hardness, are evaluated with different percentage of loadings. Incorporation of carbon does not show any major effect in the properties before and after U.V exposure, but a significant effect is observed at 2% loading of carbon black while compared to 1% and 3%.Further increase in carbon black percentage (more than 3%) will reduce the mechanical properties due to the development of stress concentration and crack propagation.